Agrobacterium Protocols Volume 1 - Wang, Kan.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
Rapid changes and significant progress have been made in the Agrobacterium field, such as genetically transforming plants for both basic research purposes and agricultural development. In Agrobacterium Protocols, Third Edition, Volumes 1 and 2, a team of leading experts and veteran researchers describe in detail techniques for delivering DNA to plant cells and permanently altering their genomes. This edition emphasizes agricultural crops and plant species with economic values, with updated protocols on 32 plant species and protocols involving 19 new species. Together with the 1st and 2nd editions, these two volumes offer Agrobacterium-mediated genetic transformation protocols for a total of 76 plant species. For a number of important plants such as rice, barley, wheat and citrus, multiple protocols using different starting plant materials for transformation are included.   Volume 1 details updated techniques available for 18 plant species drawn from cereal crops, legume plants, vegetable plants, and  three model plant species: Brachypodium distachyon, Medicago truncatula, and Setaria viridis.  It also updates a chapter for vector construction, a step critical to a successful plant transformation process.  Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.  Authoritative and cutting-edge, Agrobacterium Protocols, Third Edition  facilitates the transfer of this rapidly developing technology to all researchers for use in both fundamental and applied biology.
Gateway® Compatible Plant Transformation Vectors.- Brachypodium Distachyon -- Medicago Truncatula Transformation Using Cotyledonary Explants -- Medicago Truncatula Transformation Using Leaf Explants -- Setaria Viridis -- Barley (Hordeum Vulgare L.) Transformation Using Immature Embryos -- Barley (Hordeum Vulgare L.) Transformation Using Embryogenic Pollen Cultures -- Maize (Zea Mays L.) -- Maize, Tropical (Zea Mays L.). - Finger Millet [Eleusine Coracana (L.) Gaertn] -- Oat (Avena Sativa L.) -- Rice, Indica (Oryza Sativa L.) -- Rice, Japonica (Oryza Sativa L.) -- Sorghum (Sorghum Bicolor L.) -- Wheat (Triticum Aestivum L.) Transformation Using Immature Embryos -- Wheat (Triticum Aestivum L.) Transformation Using Mature Embryos -- Alfalfa (Medicago Sativa L.) -- Clovers (Trifolium Spp.) -- Clover, Red (Trifolium Pratense) -- Cowpea [Vigna Unguiculata (L.) Walp] -- Lentil (Lens Culinaris Medik.) -- Soybean [Glycine Max (L.) Merr.] -- Brassica Oleracea And B. Napus -- Cucumber (Cucumis Sativus L.) and Kabocha Squash (Cucurbita Moschata Duch) -- Pepper, Chili (Capsicum Annuum) -- Pepper, Chili (Capsicum Annuum) -- Pepper, Sweet (Capsicum Annuum) -- Sugar Beet (Beta Vulgaris L.) -- Tomato (Solanum Lycopersicum).
Keywords: Plant science; Botany; Plant genetics; Genetic engineering; Plant Sciences; Plant Genetics and Genomics; Genetic Engineering